PRODUCTION AND PROPERTIES OF SEVEN ADHESIVES FROM GUM ARABIC (Acacia senegal) - Umar Gwangwazo, Ibrahim; Usman, A. H.; Abubakar, A. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Adhesives are substances that are capable of holding materials via surface attachment that resist separation. They have wide applications in domestic and industrial areas. Seven different kinds of adhesives were produced using different reagents such (Na2CO3) with various concentration of 1%, 5%, and 10% designated as A,B and C, and caustic soda solution (NaOH) of 0.1M, 1M, and 5M concentrations designated as D1, D2 and D3 were prepared separately. Viscosity and drying rate of the adhesives were measured and holding capacity of each adhesive prepared were tested. From the result we observed that the seven adhesives produced has higher bonding ability on paper, wood and bank note compared to glass and ceramics since the adhesive produced are purely from the same natural resources